2008
DOI: 10.1016/j.procbio.2007.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of cross-linked tyrosinase aggregates

Abstract: The aim of this study was to prepare cross-linked enzyme aggregate (CLEA) from crude mushroom (Agaricus bisporus) extract. However, the optimization of CLEA production was performed by using pure tyrosinase. Important parameters were determined as protein, ammonium sulfate and glutaraldehyde concentrations, CLEA particle size, and cross-linking temperature and period. On the other hand, the order of ammonium sulfate and glutaraldehyde addition did not affect the yield of CLEA. Optimum CLEA preparation conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
74
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(89 citation statements)
references
References 39 publications
13
74
1
1
Order By: Relevance
“…It was observed that the maximum activity yield was obtained with 0.5% (v/v) cross-linker concentration and the highest activity of CLEA related to the native enzyme was nearly 76%. As seen in Figure 1, the activity yield of the immobilized enzyme decreased sharply with an increasing degree of glutaraldehyde, while most of the bioactivity was lost at a 9% (v/v) glutaraldehyde concentration, and the robust mechanical strength of CLEA indicated that too much extensive cross-linking occurs and the enzyme loses the minimum flexibility necessary for its activity [25]. CLEA was inflated through preparation in a high-level cross-linker agent solution that destroys active sites of the enzyme in the process of cross-linking [26].…”
Section: Glutaraldehyde Concentrationmentioning
confidence: 97%
“…It was observed that the maximum activity yield was obtained with 0.5% (v/v) cross-linker concentration and the highest activity of CLEA related to the native enzyme was nearly 76%. As seen in Figure 1, the activity yield of the immobilized enzyme decreased sharply with an increasing degree of glutaraldehyde, while most of the bioactivity was lost at a 9% (v/v) glutaraldehyde concentration, and the robust mechanical strength of CLEA indicated that too much extensive cross-linking occurs and the enzyme loses the minimum flexibility necessary for its activity [25]. CLEA was inflated through preparation in a high-level cross-linker agent solution that destroys active sites of the enzyme in the process of cross-linking [26].…”
Section: Glutaraldehyde Concentrationmentioning
confidence: 97%
“…As shown in Table 2, the apparent K M for immobilized enzyme was 1.5-fold higher for ManNAc than for free enzyme, whereas it was 2.2-fold lower for pyruvate. This differential change in affinity has also been described for the affinity of acetyl xylan esterase for 7-ACA and cephalosporin-C (Montoro- García et al, 2010), but there seem to be no clear rule, since both increases (Montoro-García et al, 2010;Shah et al, 2006) and decreases (Aytar and Bakir, 2008;Sangeetha and Abraham, 2008) in K M values have been observed in different CLEAs. These data ( Table 2) indicate that the interaction of enzyme and substrate was stronger in the case of pyruvate, and possibly, that molecular hindrances are involved in the case of ManNAc after cross-linking with glutaraldehyde.…”
Section: Kinetic Characterization Of Fastprep-cleasmentioning
confidence: 59%
“…All the CLEAs exhibited a broad bell-shape pH dependence of the catalytic activity, similar to that seen for free enzyme (Sánchez-Carrón et al, 2011), but with a pH shift towards alkaline, with an optimum of pH 7.5 in contrast to the pH 7.0 of free enzyme. This shift could have resulted from the change in acidic and basic amino acid side chain ionization in the microenvironment around the active site, which was produced by the freshly produced interaction between basic residues of the enzyme and glutaraldehyde during cross-linking, as has been previously described for tyrosinase (Aytar and Bakir, 2008), subtilin (Sangeetha and Abraham, 2008) and acetyl xylan esterase (Montoro-García et al, 2010). In addition, the stabilizing effect of BSA (Fig.…”
Section: Kinetic Characterization Of Fastprep-cleasmentioning
confidence: 89%
“…The λ in the YLL CLEAs increased with increasing (NH 4 ) 2 SO 4 saturation of the enzyme solution during precipitation, which was in agreement with Candida rugosa lipase 29 and tyrosinase. 30 When the volume ratio of (NH 4 ) 2 SO 4 solution to YLL solution increased to 4, "hyper activation" (greater than 100% λ), was observed due to the formation of more structured and fine-grained CLEAs. 31 A further increase in the ratio of the (NH 4 ) 2 SO 4 solution to the YLL solution resulted in a decrease in λ due to the larger particle size of the MCLLAs.…”
Section: Type and Quantity Of The Precipitantmentioning
confidence: 99%